Hey, I have some troubles with solving the problem below:

Let f: X -> Y and g: Y -> Z be bijective functions.

Prove that (g o f )^(-1) = f^(-1) o g^(-1).

I think I can understand it intuitively, but I don't know how to elaborate it.

Thank you.

Printable View

- April 27th 2008, 10:40 PM892kingI need help on inverse of bijective function.
Hey, I have some troubles with solving the problem below:

Let f: X -> Y and g: Y -> Z be bijective functions.

Prove that (g o f )^(-1) = f^(-1) o g^(-1).

I think I can understand it intuitively, but I don't know how to elaborate it.

Thank you. - April 28th 2008, 05:38 PM892king
I think I found the answer in other posts.

http://www.mathhelpforum.com/math-he...ons-proof.html